Aortopathy associated with congenital heart disease: A current literature review - Katrien Francois (Wolters Kluwer Medknow Publications, 2015)
In patients born with congenital heart disease, dilatation of the aorta is a frequent feature at presentation and during follow-up after surgical intervention. This review provides an overview of the pathologies associated with aortopathy, and discusses the current knowledge on pathophysiology, evolution, and treatment guidelines of the aortic disease associated with congenital heart defects.